Shear thinning and frequency-dependent behaviour of adsorbed polymer layers. Part II. Three-layer flow model. - Abdul Rashid, Suraya; Lawrence, Christoper J.; Luckham, Paul F. (Elsevier, 2008)
A novel hydrodynamic model called the three-layer flow (TLF) model has been developed to enable the quantification of viscoelastic properties of adsorbed polymer layers obtained from nanorheological experiments. By comparing the qualitative experimental data to the TLF Model, four specific parameters could be quantified from the best fit curve; these are the apparent thickness of the adsorbed layer, the real and imaginary components of the layer viscosity, and the apparent solvent viscosity. It was found that the comparison between experimental data and the TLF Model showed excellent agreement for separation distances larger than the overlap region. Furthermore, by comparing the TLF Model with experimental data at different frequencies, an apparent link was found between the complex modulus cross-over point and the adsorbed layer thickness. For adsorbed hydroxypropyl guar (HPG) layers, the cross-over point occurred when the surface separation distance was approximately equal to the thickness of a single adsorbed layer, indicating a relatively viscous nature. Finally, a direct comparison between nanorheological data with standard rheometry measurements also provided some indication of the reliability of the model.